Perspectives, aspirations and perceived support students with low economic and cultural capital in the university in Spain and Dominican Republic - José González-Monteagudo; Teresa Padilla-Carmona; María A. Tenorio-Rodríguez (European Journal for Research on the Education and Learning of Adults)
This paper investigates the characteristics and both material and emotional costs of upward social mobility through university education in Spain and the Dominican Republic. A comparative qualitative study has been carried out, based on biographical-narrative interviews, with a sample of 6 Dominican students and 9 Spanish students coming from an economically disadvantaged background. The results show the social mobility experiences and expectations of the participants and their families, with different nuances in the two contexts. The need to combine study with work is one of the main costs of university. The primary coping strategy in both countries is material and symbolic family support, but additional coping mechanisms to persist in studies are also evident. The conclusions highlight both the perspectives developed by the participants and the critical role of structural dimensions (social background, national context, recent history, economy, social values, culture, religious beliefs) in understanding their experiences in the university context.